Mortality of Invasive Pneumococcal Disease following Introduction of the 13-Valent Pneumococcal Conjugate Vaccine in Greenland - Kristiana Alexandrova Nikolova; Mikael Andersson; Hans-Christian Slotved; Anders Koch (Vaccines, 2024)
Before the incorporation of the 13-valent pneumococcal conjugate vaccine (PCV13) into the childhood vaccination regimen in Greenland in 2010, Inuit populations experienced a substantial prevalence of invasive pneumococcal disease (IPD). The PCV13 introduction has been shown to markedly reduce the incidence of IPD. This current study estimated the impact of PCV13 introduction on IPD mortality in Greenland. This was a nationwide register-based study using all available data on IPD cases 1995–2020 in Greenland. Thirty-one-day IPD case fatality rates (CFR), and all-cause and mortality rates associated with IPD during the period before the introduction of PCV13 (January 1995 to September 2010) were compared with those observed in the post-PCV13 era (September 2010 to October 2020). Standardized mortality ratios (SMRs) expressed differences in mortality by sex, age, region, ethnicity, comorbidity, and serotype. IPD CFR decreased with 24.5% from the pre- to the post-PCV13 period. SMR in IPD patients decreased by 57% (95% CI, 36–75%), and a reduction occurred in all age groups. While SMR in IPD persons ≥60 years remained virtually unchanged, there were no IPD-related deaths in persons ≤39 years in the post-PCV13 period. In conclusion, IPD-related mortality has decreased in Greenland following PCV13 introduction in 2010 in the country.